ϕ
2
(δ, s, P
T
,w
1
)
ϕ
1
(δ, s, P
T
,q,w
1
)
U
2
U
2
(δ, s, P
T
,q,h,w
1
)=h +
1
b
7
∂ϕ
1
∂δ
dδ
dt
+
∂ϕ
1
∂s
ds
dt
+
∂ϕ
1
∂P
T
dP
T
dt
+
∂ϕ
1
∂q
dq
dt
+
∂ϕ
1
∂w
1
dw
1
dt
−
−
1
T
2
b
7
ψ
2
= h +
1
b
7
∂ϕ
1
∂P
T
b
4
(−P
T
+ qC)+
∂ϕ
1
∂q
b
6
(−γ(q) − b
5
s + h)
+
+
1
b
7
∂ϕ
1
∂δ
s +
∂ϕ
1
∂s
b
1
(P
T
− E
2
q0
y
11
sin(α
11
) − E
q0
U
c
y
12
sin(δ − α
12
)+w
1
)
+
+
1
b
7
∂ϕ
1
∂w
1
ξs −
1
T
2
b
7
(h − ϕ
1
(δ, s, P
T
,q,w
1
)).
ϕ
1
(δ, s, P
T
,q,w
1
)
T
i
> 0,i= 1, 3; λ
1
> 0,λ
2
> 0,γ
1
> 0.
δ(0) = 1, 728 s(0) = 0 E
q
(0) = 1.78
P
T
(0) = 0, 7 q(0) = 0, 7 h(0) = 0, 7 w
1
(0) = 0
x
d
=2, 5 x
d
=0, 28 r =0, 003 r
c
=0, 6 x
c
=0, 8 C =1, 2 k
ω
=20
k
q
=1 ω
0
=1 Tj =9, 17 T
d0
=6 T =4 T
c
=0, 4 T
B
=0, 25 U
c
=1
U
0
=1, 1 T
1
=1 T
2
= T
3
=5 λ
1
= λ
2
=4 γ
1
= ξ =1
0, 1 U
1
3 0 U
2
1
M(t)
P
T
(t)